Выбор критических сечений электрических проводов и кабелей в силовых цепях электрооборудования промышленной электроэнергетики - Баранов, Михаил Иванович (Национальный технический университет "Харьковский политехнический институт", 2019)
Приведены результаты разработанного электротехнического подхода к расчетному выбору по условию электрического взрыва (ЭВ) токонесущих частей кабельно-проводниковой продукции критических сечений SCi не изолированных проводов, а также изолированных проводов и кабелей с поливинилхлоридной (ПВХ), резиновой (Р) и полиэтиленовой (ПЭТ) изоляцией с медными(алюминиевыми) жилами(оболочками), по которым в силовых цепях электрооборудования общепромышленного назначения в аварийном режиме протекает ток ik(t) короткого замыкания (КЗ) с заданными амплитудно-временными параметрами (АВП). На основании данного подхода осуществлен реальный выбор критических сеченийSCi для указанных проводов (кабелей) силовых цепей рассматриваемого электрооборудования. Выполнена расчетная численная оценка критических амплитуд плотностей δCi тока ik(t) КЗ с заданными АВП в проводах и кабелях силовых цепей указанного электрооборудования. Полученные данные будут способствовать обеспечению термической стойкости электрических не изолированных проводов, а также проводов и кабелей с ПВХ, Р и ПЭТ изоляцией, широко применяемых в силовых цепях электрооборудования общепромышленного назначения.

Purpose.Implementation of close calculation determination of critical sections of SCiand critical amplitudes of density of al-ternating current δCiof frequency 50 Hz in wires and cables of power circuits of electrical equipment of power industry, char-acterized flowing in it at malfunctions of operation current ik(t) of short circuit (SC) with set amplitude-temporal parameters (ATP). Methodology.Scientific and technical bases of power engineering, electrophysics basesof technique of high-voltage and large pulsed currents, theoretical bases of the electrical engineering. Results.The results of the developed electrical engineering approach are resulted in a calculation choice on the condition of electric explosion (EE) of current-carrying parts of cable and conductor products (CCP) of critical sections of SCifor the copper (aluminum) cores of the uninsulated wires, and also for the insulated wires and cables with a polyvinilkhlo-ride (PVC), rubber (R) and polyethylene (PET) insulation with copper (aluminum) cores (shells) on which in the power circuits of electrical equipment of the general industrial equipment in malfunction the current of SC ik(t) flows with set ATP. On the basis of determination of sizes of the real critical sections SCifor the indicated wires and cables the calculation numeral estima-tion of critical amplitudes of density δCiof SC current ik(t) is executed with set ATP in current-carrying parts of investigated CCP of power circuits of the examined electrical equipment. It is determined that in the power circuits of electric equipment of the general industrial installations (for permanent time of slump of Ta=50 ms of аperiodic to the constituent of current of SC) critical amplitudes of density δCiof SC current ik(t) at time of his disconnecting tk=100 ms in copper (aluminum) cores for the uninsulated wires and insulated wires (cables) with copper (alu-minum) cores (shells), PVH, R and PET it is numeral made an insulation according to approximately 1,57 (1,18) kA/mm2. At time of disconnecting tk=160 ms of SC current ik(t) in the power circuits of the examined electrical equipment (Ta=50 ms) criti-cal amplitudes of density δCiof SC current ik(t) for the copper (aluminum) cores (shells) of indicated CCP become accordingly numeral equal approximately 1,33 (0,99) kA/mm2. Originality.First by a calculation way taking into account information for ATP of SC current ik(t) and quantitative values of time of his disconnecting tkin the power circuits of electrical equipment of the general industrial installations the numerical values of criti-cal sections SCiand critical amplitudes of density δCiof AC SC current ik(t) are certain for the uninsulated wires, and also insu-lated wires and cables with copper (aluminum) cores (shells), PVH, R and PET insulation. Practical value.Obtained results for the critical sections SCiand amplitudes of density δCiof AC SC current ik(t) of frequency 50 Hz (at the period of oscillations of Tp=20 ms for of periodic constituent of emergency current of SC) can be utilized in power industry in practice at a choice thermally by a bar to the action of large SC currents ik(t) of CCP with copper (aluminum) bars (shells), intended for reliable operation in the power circuits ofelectrical equipment of industrial power industry.
A choice of critical sections of electric wires and cables in power circuits of electrical equipment of power industry
Keywords: расчетный выбор критических сечений проводов и кабелей в цепях электрооборудования; calculation choice of critical sections of wires and cables in the circuits of electrical equipment